Pengembangan Sistem E-Learning Menggunakan Metode Research & Development Pada MTs. Roiyatul Mujahidin - Wahyu Hadikristanto; Nur Azizah; Aswan S Sunge (Jurnal SIGMA, 2022)
MTs Roiyatul Mujahidin is a tsanawiyah madrasa that forms quality human resources (HR). The learning system that takes place at MTs Roiyatul Mujahidin is done face-to-face and there is no online learning media that utilizes information technology that supports students' understanding of the main lessons by the teacher. The problem that has occurred so far is the ineffectiveness of teaching and learning activities in schools, so there is a need for additional hours of learning. Therefore, it is necessary to create a Web-Based E-Learning Information System at MTs ROIYATUL MUJAHIDIN using PHP and MySQL dataase which can be accessed anytime and anywhere so as to support the educational process at MTs Roiyatul Mujahidin and facilitate the dissemination of knowledge to students. E-Learning is a distance learning using internet technology, the development method used by the author is the Research & Development method, which is a method that uses a systematic and sequential approach starting from the development carried out in several stages, namely design, production, and evaluation. Keywords: Employee Recruitment, Classification, C5.0 Algorithm